2014
DOI: 10.1007/s11284-014-1190-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fitness costs of resistance against the parasitoid Leptopilina victoriae in Drosophila bipectinata

Abstract: How insects evolve resistance or counter-resistance against antagonists is a basic issue in the study of host-parasitoid coevolution. One of the factors that affect their coevolution is fitness costs of resistance and counter-resistance. Here, we assess fitness costs of resistance against the parasitoid Leptopilina victoriae in Drosophila bipectinata on the basis of selection experiments. We made a base population by mixing three geographic fly populations that differed in resistance. After six generations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Novković et al (2012) reported that a population of D. bipectinata from Iriomote-jima (IR: Japan) was susceptible to L. victoriae from Kota Kinabalu (L. victoriae KK), but those from Kota Kinabalu (KK: Malaysia) and Bogor (BG: Indonesia) were resistant to this parasitoid population. The number of genes causing this difference in resistance may be few, because an experimental population produced by mixing these IR, KK and BG populations rapidly responded artificial selection for increased resistance against L. victoriae KK in our previous study (Takigahira et al 2014). In this study, we verify this notion by cross experiments using the resistant KK and susceptible IR populations.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Novković et al (2012) reported that a population of D. bipectinata from Iriomote-jima (IR: Japan) was susceptible to L. victoriae from Kota Kinabalu (L. victoriae KK), but those from Kota Kinabalu (KK: Malaysia) and Bogor (BG: Indonesia) were resistant to this parasitoid population. The number of genes causing this difference in resistance may be few, because an experimental population produced by mixing these IR, KK and BG populations rapidly responded artificial selection for increased resistance against L. victoriae KK in our previous study (Takigahira et al 2014). In this study, we verify this notion by cross experiments using the resistant KK and susceptible IR populations.…”
Section: Introductionmentioning
confidence: 58%
“…The selected and control populations were maintained under 15L: 9D at 23°C. At the 10th generation, the rate of successful parasitism by L. victoriae KK was less than 10 % in selected (resistant) populations and approximately 85 % in control (susceptible) populations (Takigahira et al 2014).…”
Section: Laboratory Populationsmentioning
confidence: 97%
See 3 more Smart Citations